Diplomatic terminology: lexicographic problems - M V Belyakov (RUDN Journal of Language Studies, Semiotics and Semantics, 2012)
Language of diplomacy is rather complex and unusual system which lexicon combines an abundance of diverse terms - diplomatic, historical, culturological, linguistic, legal and of some others. In this article the lexicographic description of two terminological diplomatic dictionaries is represented, some concepts, specific terms of the dictionaries are classified, the usage possibility of the dictionaries is estimated concerning the modern diplomatic texts published on a site the Ministry of Foreign Affairs of the Russian Federation.